Matriarchy in Bronze Age Crete : a perspective from archaeomythology and modern matriarchal studies - Cichon, Joan Marie (Archaeopress Archaeology, 2022)
This text makes a compelling case for a matriarchal Bronze Age Crete. It is acknowledged that the preeminent deity was a Female Divine, and that women played a major role in Cretan society, but there is a lively, ongoing debate regarding the centrality of women in Bronze Age Crete. a gap in the scholarly literature which this book seeks to fill.